Paired analysis of flexible and navigable suction ureteral access sheath vs. conventional ureteral access sheath, both combined with needle-perc assisted endoscopic surgery, for the treatment of <2 cm lower calyceal stones with unfavorable anatomy - Luo, Daxun; Xu, Zheng; Ding, Tianfu; Liu, Yubao; Li, Jianxing (Frontiers in Surgery, 2025)
PurposeTo compare the flexible and navigable suction ureteral access sheath (FANS) with the conventional ureteral access sheath, both in combination with Needle—perc Assisted Endoscopic Surgery (NAES), for treating <2 cm lower calyceal stones with unfavorable anatomy.Materials and methodsData of patients admitted to Beijing Tsinghua Changgung Hospital with <2 cm stones with unfavorable anatomy of the renal lower calyx from August 2023 to May 2024 were collected retrospectively, and matched parameters such as age, gender, BMI, stone size, CT values, laboratory tests, and anatomical features of the lower calyces of the kidney were recorded. Both groups of patients were treated with NAES, and patients who were treated with FANS were compared with those who received a conventional ureteral access sheath in a pairwise analysis (1:1). Data were analyzed using t-test, Mann–Whitney U-test, and chi-square test.ResultsBoth groups had similar baseline characteristics. The immediate stone-free rate (SFR) was better in the FANS group than in the conventional ureteral access sheath treatment group (88% vs. 64%, p = 0.044). The duration of surgery was shorter in the former than in the latter in both groups (100.75 ± 25.32 min vs. 116.21 ± 35.56 min, p = 0.048). No statistically significant differences were observed between the two groups in postoperative ESWL treatment, postoperative creatinine, hospital stay, 1-month SFR, and complication rates.ConclusionsIn the NAES procedure, compared with conventional ureteral access sheath, the FANS ensures safety while also demonstrating greater effectiveness for treating kidney stones in patients with unfavorable renal lower calyx anatomy of less than 2 cm.